Greenwich Park [large type] - Faulkner, Katherine (Thorndike Press large print core series., 2022)
"A twisty, whip-smart debut thriller, as electrifying as the #1 New York Times bestseller The Girl on the Train, about impending motherhood, unreliable friendship, and the high price of keeping secrets. Helen's idyllic life--handsome architect husband, gorgeous Victorian house, and cherished baby on the way (after years of trying)--begins to change the day she attends her first prenatal class and meets Rachel, an unpredictable single mother-to-be. Rachel doesn't seem very maternal: she smokes, drinks, and professes little interest in parenthood. Still, Helen is drawn to her. Maybe Rachel just needs a friend. And to be honest, Helen's a bit lonely herself. At least Rachel is fun to be with. She makes Helen laugh, invites her confidences, and distracts her from her fears. But her increasingly erratic behavior is unsettling. And Helen's not the only one who's noticed. Her friends and family begin to suspect that her strange new friend may be linked to their shared history in unexpected ways. When Rachel threatens to expose a past crime that could destroy all of their lives, it becomes clear that there are more than a few secrets laying beneath the broad-leaved trees and warm lamplight of Greenwich Park"--